ANALYSIS OF FACTORS INFLUENCING THE OCCURRENCE OF FRAUD IN COVID-19 SOCIAL FUND ASSISTANCE IN THE CITY OF MALANG - Moh Cholid Mawardi (Cita Konsultindo Research Center, 2023)
This research was conducted to determine the factors of pressure, opportunity, and rationalization that affect the occurrence of the covid-19 social fund assistance fraud in the Malang City environment. The sample in this study were active employees of regional work units in social services, districts and villages of Malang City. The type of research in the preparation of this paper is correlational research. The analytical method used is Multiple Linear Regression with SPSS 26 Software For Windows. Based on the result of research and discussion that has been done, it can be concluded that pressure, opportunity, and rationalization have a positive and significant effect on the fraud of covid-19 social fund assistance in the Malang City environment.